(untitled) (Research, Society and Development, 2022)
The appropriate time for leaf collection to evaluate the nutritional status of the coffee tree should be carried out when the nutrient is in higher levels in the leaves, which may vary according to the phenological stage of the fruits. Macro and micronutrients do not show the same pattern regarding the period of highest leaf content. Therefore, it is coherent to define different times of leaf collection for each nutrient. The objective of this study was to verify the most suitable times for collecting leaves to evaluate the nutritional status of coffee plants based on the phenological development of coffee fruits. The experiment was carried out in a commercial field, in which six coffee cultivars were used (Acauã Novo, Bourbon Amarelo, Catuaí Vermelho IAC 144, Catucaí 20/15, IAC 125 RN and IPR 100). The collections were carried out in four phenological phases of coffee fruit development (floral bud maturation, chumbinho, fruit expansion, and fruit granulation). The periods with the highest concentrations varied based on the phenological stages of the fruits, and differences in concentrations were also observed between the cultivars examined. The highest zinc concentration in the leaves was observed in the maturation phase of the floral bud. Foliar collection for the diagnosis of the nutritional state of the coffee plant should be done for each nutrient based on the phenology of the fruits.